Pengaruh Penerapan Metode Scramble dalam Pembelajaran Nahwu terhadap Pemahaman Siswa - Trismawati, Irma; Nurhamim, Nurhamim; Ubaidillah, Ubaidillah (Pendidikan Islam Anak Usia Dini STIT Palapa Nusantara, 2025)
The purpose of this study was to examine how the use of the Scramble technique affects students' understanding of Nahwu. An experiment with a quantitative design was the methodology used in this study. A total of 56 students were sampled, divided into two groups: the experimental group, which used the Scramble approach, and the control group, which used the traditional method. A written test with questions regarding Nahwu content and observations was used as a data collection tool. The results of the pre-test and post-test were collected, and a t-test was used to analyze the data and determine whether the pre-test and post-test results of the two groups were different. The findings showed that students' understanding of Nahwu content increased significantly after the application of the method.